YOUTH ORGANIZATION IN UZBEKISTAN - Sayliyeva Gulchiroy Sohibzhanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, we wrote about youth organization in Uzbekistan when created this organization, why created it, what it’s doing nowadays, what it did.